2016
DOI: 10.3168/jds.2015-10098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stocking density on behavior, productivity, and comfort indices of lactating dairy cows

Abstract: The objective of this study was to investigate the effects of different stocking densities of 82 (0.82 cows per freestall and feed bin), 100, and 129% on behavior, productivity, and comfort indices of lactating Holstein dairy cows. Twenty-seven lactating cows (15 primiparous and 12 multiparous) were assigned to 1 of the 3 treatments, which were balanced for parity, milk yield, days in milk, and body weight in a 3×3 Latin square design with 14-d periods. After 7 d of adaptation to the treatments, lying time and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 35 publications
4
30
1
2
Order By: Relevance
“…We expected that SD lower than 100% should be provided to early lactating cows for lowering their oxidative stress, although 100% SD had higher efficiency in space utilization. Through determining oxidative stress index in the plasma and milk, our study suggested that in addition to reducing rumination (Wang et al, 2016), inhibiting lying behaviour (Krawczel et al, 2012) and disturbing comfortability (Krawczel et al, 2008) of the dairy cows, higher SD triggered oxidative stress of early lactating dairy cows.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We expected that SD lower than 100% should be provided to early lactating cows for lowering their oxidative stress, although 100% SD had higher efficiency in space utilization. Through determining oxidative stress index in the plasma and milk, our study suggested that in addition to reducing rumination (Wang et al, 2016), inhibiting lying behaviour (Krawczel et al, 2012) and disturbing comfortability (Krawczel et al, 2008) of the dairy cows, higher SD triggered oxidative stress of early lactating dairy cows.…”
Section: Discussionmentioning
confidence: 86%
“…It is known that overstocking of dairy cows necessarily impact natural resting behavior of dairy cows (Špinka, ). The troubles caused by high SD included reduced rumination (Wang et al., ), insufficient lying time (Krawczel et al., ), and lower comfortability (Krawczel, Hill, Dann, & Grant, ) in mid‐lactating dairy cows. Recent studies suggested that overstocking also have negative impact on calves or transition cows, which were in critical physiology stages.…”
Section: Introductionmentioning
confidence: 99%
“…This could be associated with the presence of subclinical or clinical mastitis, which increases the electrical conductivity of milk. Wang et al (2016) observed that the milk somatic count of the cows increased by 12.26% when stocking density was increased to 124%. Milking duration during that period was higher than during the comparison period despite the lower milk yield.…”
Section: Resultsmentioning
confidence: 97%
“…A considerable decrease (8.92 kg) in daily milk production was observed in the second experimental period when twice as many cows were introduced compared to the first period (P ≤ 0.01). Wang et al (2016) observed that when stocking density increased from 100 to 129%, milk yield increased from 31.91 to 33.11 kg. De Vries et al (2016) reported that for a density of 150%, daily milk yield per cow decreased from 28.48 to 26.38 kg.…”
Section: Resultsmentioning
confidence: 99%
“…The increased NDF:NFC ratio was correlated with decreased (P < 0.05) DMI between 00:00-06:00 prepartum and increased (P = 0.09) DMI between 18:01-24:00. Other studies have also found that dairy cows had lower DMI between 00:00-06:00 (Wang et al, 2016), finishing steers spent more time on eating during day time than the night time (Yazdani and Hajilari, 2009).…”
Section: Distribution Of Dmimentioning
confidence: 90%